The Literacy Practice and Religious Proselytizing in Nineteenth-Century Indonesia: A Study on the Kitabs of KH. Ahmad Rifa’i Kalisalak - Mustolehudin, Mustolehudin; Iswanto, Agus; Noviani, Nurlaili; Masfiah, Umi; Hidayat, Roch Aris; Maknun, Moch Lukluin; Ruchani, Bisri; Ridlo, Subkhan (Proceedings of International Conference on Da'wa and Communication, 2020)
There weren’t many scholars who studied the history of Indonesian literacy practices, even though the written sources were available abundantly. The existed studies from many scholars less concerned about the relationship between literacy practice and religious proselytizing (da’wa) in Indonesia. Whereas, both of them are closely related in Indonesia literacy practices, especially in Indonesia’s pre-contemporary era. This study aims to emphasize the relation between literacy practices and Islamic da’wa through KH. Ahmad Rifai works. He was a prolific Muslim scholar in the 19th century who wrote many religious books and countered colonialism. This study reviewed Ahmad Rifai books through a new literacy practice perspective. The argument of this study is the literacy practices had a tight relation with Islamic proselytizing in Indonesian history. The literacy practice for da’wa often considers the locality in culture. Therefore, the form of literacy practice that emerges is a form of literacy that considers local languages and writings, which in this case is the Javanese language and the Pegon script. This paper gives a contribution to the discussion between accommodative da’wa and literacy practices.